2012
DOI: 10.1177/0003319711436247
|View full text |Cite
|
Sign up to set email alerts
|

Relation Between Mean Platelet Volume and Severity of Atherosclerosis in Patients With Acute Coronary Syndromes

Abstract: Platelets play a central role in the pathophysiology of coronary artery disease (CAD). Increased mean platelet volume (MPV) is an indicator of platelet function and associated with poor clinical outcome in patients with acute coronary syndrome (ACS). We evaluated the relationship between MPV and severity of CAD in patients with ACS. A total of 395 patients with ACS were included. Severity of CAD was assessed with the Gensini and Syntax scores. High levels of MPV were associated with the Gensini and Syntax scor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
58
2
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(68 citation statements)
references
References 31 publications
3
58
2
5
Order By: Relevance
“…These mediators can contribute to inflammation and atherogenesis and may explain the association between MPV and atherosclerosis. It has been previously shown that larger platelets are associated with severity of CAD [31], PAD [32][33], and carotid atherosclerosis [34][35]. Possible mechanism for correlation of larger platelets with ischemic stroke as shown in our study may be the augmented rate of atherosclerosis unlike atrial fibrillation or other prothrombotic conditions.…”
Section: Discussionsupporting
confidence: 64%
“…These mediators can contribute to inflammation and atherogenesis and may explain the association between MPV and atherosclerosis. It has been previously shown that larger platelets are associated with severity of CAD [31], PAD [32][33], and carotid atherosclerosis [34][35]. Possible mechanism for correlation of larger platelets with ischemic stroke as shown in our study may be the augmented rate of atherosclerosis unlike atrial fibrillation or other prothrombotic conditions.…”
Section: Discussionsupporting
confidence: 64%
“…trombosit hacminin arttığı gösterilmiştir 6,7 . Bizim çalışma-mızda MPİ ile CRP ve MPV arasında anlamlı ilişki tespit edilmemiştir.…”
Section: Discussionunclassified
“…Son zamanlarda yapılan bazı çalışmalarda akut miyokard infarktüsü, kararsız angina pektoris, iskemik kalp hastalığı ve konjestif kalp yetmezliğinde ortalama trombosit hacminin arttığı gösterilmiş olup, diğer açıdan son yıl-larda CRP'nin kardiyovasküler açıdan proaterojenik ve prognostik özelliklere sahip olduğunu gösteren bir çok çalışma yayınlanmıştır [6][7][8] . Bu çalışmada kardiyovasküler açıdan prognozu etkileyici bir risk faktörü olarak düşü-nülen (myokard performans indeksi) MPİ'nin CRP ve MPV ile arasındaki ilişki araştırıldı.…”
unclassified
“…[30][31][32] Increased MPV levels are also associated with complex coronary lesions. 4,7,33 Ekici et al 4 reported that MPV was associated with the angiographic severity of CAD in patients with elective CA. Sahin et al 7 found that the relation between MPV and SXscore in diabetic patients with STEMI was stronger than for nondiabetic patients with STEMI.…”
Section: Discussionmentioning
confidence: 99%